Virtual Reality in Natural Sciences - Karme, Aleksis; Happonen, Paavo (LUMAT-B: International Journal on Math, Science and Technology Education, 2017)
Virtual and augmented reality is a hot topic in education and research. To reach educators in natural sciences, Teatime Research Ltd and Department of Geosciences and Geography from the University of Helsinki organized a workshop during the LUMAT Symposium 2017. The participants were shown the possibilities of the technologies and software available, one of these being the locally developed Teatime Vrifier, a universal viewer for three dimensional data. To integrate these new technologies into educational workflows and daily use, it requires actual testing and exposure on all levels.